Characteristics associated with physical activity among independently ambulant children and adolescents with unilateral cerebral palsy - Mitchell, L.; Ziviani, J.; Boyd, Roslyn (2014)
Aim: This study aimed to quantify the contribution of physical, personal and environmental characteristics to physical activity among independently ambulant children with unilateral cerebral palsy (CP). Method: One-hundred and two children with unilateral CP (52 males, 50 females; 52 right hemiplegia; mean age 11y 3mo, range 8–17y [SD 2y 4mo]) classified at Gross Motor Function Classification System (GMFCS) levels I = 44 and II = 58 participated. Physical activity was measured over 4 days using ActiGraph accelerometers recording as activity counts. GMFCS, functional strength, 6-minute walk test (6MWT), mobility limitations (MobQues28), age, sex, Assessment of Life-Habits recreation domain, Participation and Environment Measure for Children and Youth (PEM-CY) and environmental characteristics were considered for selection in a linear regression model. These served as independent variables which were determined using a backwards selection procedure. Results: Younger age, male sex, increased performance on the 6MWT, and increased participation in the home and community measured using the PEM-CY were significantly associated with activity counts (p<0.001). However, the model fit was somewhat weak (R2=0.32), indicating that much of the variation was unexplained. Older age and reduced community participation were associated with high inactivity (p<0.001). Interpretation: Physical activity interventions should primarily target adolescents and females. Walking endurance and participation in the home and community may represent modifiable characteristics to increase physical activity.